Influence of fluidity improver on metal-polymer direct joining via injection molding - Wang, Shuohan; Kimura, Fuminobu; Zhao, Shuaijie; Yamaguchi, Eiji; Ito, Yuuka; Kajihara, Yusuke (Precision engineering, 2021)
Injection molded direct joining (IMDJ) is one type of metal-plastic direct joining methods. IMDJ first treats the metal surface and then injects melted polymer onto the surface via injection molding technology. IMDJ method is excellently suitable for a mass production environment for the injection molding technology characteristics of high-speed production. However, one of the factors limiting the application of IMDJ is its low joining strength. In this study, we improved joining performance by mixing a flow modifier (flow modifier OSGOL MF-11) in the engineering polymer polyamide 6 (PA6). We studied the influence of the additive amount on the joining strength. It was found that mixing OSGOL MF-11 in PA6 is a feasible method to improve the joining strength, with maximum improvement by up to 75%. The mechanical interlocking improvement by higher fluidity was confirmed by cross-sectional analysis. FTIR spectra analysis results showed the possibility of chemical interaction occurrence, which causes the joint to be more robust. Materials modification by additives is much easier to apply compared to modification processing technology. The results provide new ideas for IMDJ development. •Polymer modification by additives in injection molding direct joining technology.•Flow modifier to PA6 greatly enhances the metal-polymer hybrid joining strength.•The joining strength was improved by better mechanical interlocking effect.•The possibility of chemical interaction at joint interface was found.